Public oversight of the audit profession – Comparison of implemented practices in the EU and the U.S. - Maja Zaman Groff; Marko Hočevar (Central European Public Administration Review)
Following financial scandals at the turn of the century, the audit profession in the European Union, the United States and elsewhere, has undergone profound legislative and regulatory reforms, including the requirement for intense public oversight of the profession. The article provides an overview of the development of external quality assurance systems in the audit profession in the EU and the U.S. with emphasis on the system of public oversight, implemented after the passing of the Sarbanes-Oxley Act of 2002 in the U.S. and the Statutory Audit Directive of 2006 in the EU. The aims of the article are: 1) to explain different backgrounds of external quality assurance systems in the EU and the U.S., 2) to describe implemented practices related to the public oversight system in the two regions and 3) to present the main findings of the existing empirical research focusing on the impact of the newly established systems of public oversight on the quality of audit services. Our literature research reveals that the evidence on the impact of the public oversight on the ultimate audit quality in the EU has not yet been provided because the Member States have only finished the implementation of the Statutory Audit Directive requirements into national legislations by the year 2008. In the U.S., on the other hand, first empirical evidence has been presented, suggesting that the quality of auditing has improved after the passing of the Sarbanes Oxley Act of 2002. So far evidence has been provided to support the proposition that PCAOB opinions are associated with earnings quality of the audit firm’s clients, that auditors have become more conservative and that the new inspectors (as opposed to the former system of self-regulation) can hold the auditors to stricter standards by taking concrete actions against felonious auditors and imposing costly penalties.